Zaprta in odprta dramska forma pri Cankarju - Zemljarič Miklavčič, Jana (Primerjalna književnost, 1999)
Closed and Open Dramatic Form in Cankar. - The main objective of this essay is a through formal-aesthetic analysis of three plays by Ivan Cankar, Kralj na Betajnovi (1901), Pohujšanje v dolini šentflorjanski (1907) and Lepa Vida (1911). Applying Klotz's theory on closed and open dramatic form I have analysed the dramatic categories of place, time, character, act, composition and language, and gained an insight into the basic structure of Cankar's drama. The results of an individual analysis of each play were explained from the position of the entire dramatic text in its historical context. Dramatic form, as the only entirely tangible constituent part of the work of art, was taken as the basis on which to build an interpretation of an individual text, or an extract. Fairly detailed examples of both ideal types were discovered: Kralj na Betajnovi can be labelled as having a predominantly closed dramatic form, and Lepa Vida as mainly open. I was particularly interested in the modifications of both ideal types, in which the author's creativity and originality was recognised.
Keywords: Cankar, Ivan, 1876-1918; literarna teorija; literarne študije; literary theory; Slovene literature; slovenska dramatika; slovenska književnost; teorija drame